CAFF CBMP Report No.14 --- CBMP Implementation Plan - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF, 2009)
Arctic Council's CAFF Circumpolar Biodiversity Monitoring Plan Report No.14 CBMP Implementation Plan